2006
DOI: 10.1158/1055-9965.epi-05-0913
|View full text |Cite
|
Sign up to set email alerts
|

Gonorrhea, Syphilis, Clinical Prostatitis, and the Risk of Prostate Cancer

Abstract: Background: Although previous case-control studies have observed positive associations among gonorrhea, syphilis, clinical prostatitis, and prostate cancer, many may have been susceptible to recall and interviewer biases due to their retrospective designs. Therefore, to investigate these associations without concerns of recall and interviewer biases, we conducted a large, prospective investigation in the Health Professionals Follow-up Study. Methods: In 1992, participants were asked to report their histories o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
71
2
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 37 publications
7
71
2
3
Order By: Relevance
“…Based on participants' lower reported lifetime prevalence of STIs, which we have previously hypothesized also reflects a lower likelihood of repeat and coinfections [32], as well as their education, socio-economic status, and race/ethnicity, we postulated that histories of gonorrhea and syphilis in this cohort likely reflected only one or two episodes of treated infection with a low likelihood of co-infections. Therefore, our findings suggested that low exposure to gonorrhea and syphilis does not increase risk of prostate cancer [55]. These findings were supported by subsequent results in the Prostate, Lung, Colorectal and Ovarian (PLCO) Cancer Screening Trial, in which the authors observed no association for a history of gonorrhea, and an unstable, possibly inverse association for a history of syphilis among Caucasian participants, who had similarly low reported lifetime prevalences of infection as HPFS participants.…”
Section: Information Biassupporting
confidence: 83%
See 1 more Smart Citation
“…Based on participants' lower reported lifetime prevalence of STIs, which we have previously hypothesized also reflects a lower likelihood of repeat and coinfections [32], as well as their education, socio-economic status, and race/ethnicity, we postulated that histories of gonorrhea and syphilis in this cohort likely reflected only one or two episodes of treated infection with a low likelihood of co-infections. Therefore, our findings suggested that low exposure to gonorrhea and syphilis does not increase risk of prostate cancer [55]. These findings were supported by subsequent results in the Prostate, Lung, Colorectal and Ovarian (PLCO) Cancer Screening Trial, in which the authors observed no association for a history of gonorrhea, and an unstable, possibly inverse association for a history of syphilis among Caucasian participants, who had similarly low reported lifetime prevalences of infection as HPFS participants.…”
Section: Information Biassupporting
confidence: 83%
“…However, more prospective studies are now beginning to be conducted. In 2006, we published the results of our prospective cohort investigation in the Health Professionals Follow-up Study (HPFS), in which we observed no association for a history of gonorrhea and an unstable, null association for a history of syphilis and risk of prostate cancer [55]. Based on participants' lower reported lifetime prevalence of STIs, which we have previously hypothesized also reflects a lower likelihood of repeat and coinfections [32], as well as their education, socio-economic status, and race/ethnicity, we postulated that histories of gonorrhea and syphilis in this cohort likely reflected only one or two episodes of treated infection with a low likelihood of co-infections.…”
Section: Information Biasmentioning
confidence: 99%
“…Since the latter evidence suggested the existence of a detection bias in the patient population, subsequent subset analyses were performed by considering only men screened for prostate cancer. In this context, a significant association was found between PCa and a history of clinical prostatitis among men diagnosed for PCa <59 years of age (22). In summary, analysis by age revealed significant links that may have been overlooked in studies performed on a non-stratified population.…”
Section: Clinical and Epidemiological Studiesmentioning
confidence: 79%
“…A large prospective study reported in 2006 by Sutcliffe and coworkers, based on data collected in the frame of the Health Professional Follow-up Study, included 5,732 patients with and 29,854 patients without prostatitis (22). Although the study failed to show an overall link between prostatitis and prostate cancer, it demonstrated a positive significant association between these conditions in the younger male population.…”
Section: Clinical and Epidemiological Studiesmentioning
confidence: 99%
“…History of prostatitis (OR 25.0, 95% CI 9.2-67.9) was observed to be positively associated with prostate cancer risk (Hosseini et al, 2010). On the other hand many prospective studies have not shown any significant association between history of gonorrhea or syphilis and prostate cancer (Huang et al, 2008;Sutcliffe et al, 2006). In different studies, the frequency of sexual activity has been found to have direct relationship with the development of prostate cancer.…”
Section: Sexual Behavior and Sexually Transmitted Diseasesmentioning
confidence: 99%